Successful Elite Sport Policies: Indonesia at The 2018 Asian Games - Adi Rahadian; Amung Ma’mun; Berliana Berliana; Nuryadi Nuryadi (JUARA : Jurnal Olahraga, 2021)
The government fully supports efforts to carry out the best achievements in a sustainable, systematic, and integrated way by involving all of the nation's potentials and strengths. This study aims to identify and analyze the main determinants of the success of elite sports policies in Indonesia. A qualitative approach with a case study design was chosen in this study. Observations, semi-structured interviews, and document analysis were used in data collection in which academics, elite athletes, and coaches were participants in this study. These findings show that efforts to integrate the success pathway of coaching and to develop exceptional sports achievements at the 2018 Asian Games (Presidential Decree No. 95 of 2017) are managed systematically, professionally, and become a shared commitment. As a result, Indonesia was successfully ranked 4th in Asia with 31 gold, 24 silver, and 43 bronze medals. So that, the slogan "Energy of Asia" has transformed into a generator of Indonesia in successful implementation, achievement, administration, and economic empowerment.